Antisecretory Action of the Extract of the Aerial Parts of Eremomastax speciosa (Acanthaceae) Occurs through Antihistaminic and Anticholinergic Pathways - Amang André Perfusion; Paul V. Tan; Nkwengoua Ernestine; Nyasse Barthélemy (Advances in Pharmacological Sciences)
Objective. The objective of this study was to find out the possible antiulcer mechanism of action of Eremomastax speciosa. Method. Carbachol- and histamine-induced hypersecretion, associated with the pylorus ligation technique, were used in rats. Gastric mucosal ulceration, mucus production, pH, gastric volume, and acidity were measured. Results. Histamine and carbachol raised gastric acidity to 86.50 and 84.80 mEq/L, respectively, in the control rats, and the extracts (200 mg/kg) reduced gastric acidity to 34.60 and 39.00 mEq/L, respectively. Intraduodenal aqueous extract (400 mg/kg) in histamine- and carbachol-treated rats produced significant (P<0.001) decreases in acid secretion to 28.50 and 28.80 mEq/L, respectively, and 100 percent inhibition of gastric ulceration. Augmented histamine-induced gastric acid secretion (90.20 mEq/L) was significantly reduced to 52.60 and 27.50 mEq/L by the 200 and 400 mg/kg doses of the aqueous extract, respectively. The extract significantly reduced (P<0.001) the volume of gastric secretion and significantly increased mucus production. The ulcer inhibition potential of the extract significantly dropped to 25–44% (oral extract) and to 29–37% (duodenal extract) in carbachol/indomethacin-treated rats. Conclusion. The aqueous extract of E. speciosa has both cytoprotective and antisecretory effects. The antisecretory effect may involve a mechanism common to both cholinergic and histaminergic pathways.